Pengaruh Pengetahuan Dan Lingkungan Wajib Pajak Terhadap Kepatuhan Wajib Pajak - Gessy Ghesiyah (Jurnal Riset Akuntansi dan Keuangan, 2022)
Abstract. This study aims to determine whether knowledge of taxation and the taxpayer environment has an effect on taxpayer compliance through taxpayer awareness as an intervening variable. The research method used is explanatory research. The type of research data in the form of primary data is by giving a questionnaire. The population in this study is the Marketplace registered in the membership directory of the Indonesian E-Commerce Association (idEA). And the sample in this study there are 53 companies. The results of partial hypothesis testing indicate that tax knowledge has a significant effect on taxpayer awareness and the taxpayer environment has a significant effect on taxpayer awareness. The results of partial hypothesis testing indicate that tax knowledge has a significant effect on taxpayer compliance and the taxpayer environment has a significant effect on taxpayer compliance. Simultaneous hypothesis testing results show that Tax Knowledge Indirect Positive Effect on Taxpayer Compliance with Taxpayer Awareness as an Intervening Variable while the Taxpayer's Environment does not Indirectly Positive Effect on Taxpayer Compliance with Taxpayer Awareness as an Intervening Variable.